Maastricht and the codecision procedure : success story. - BOYRON, Sophie (1996)
Provides in-depth study of Article 1896 of the EC Treaty - codecision procedure, and analyses the real impact of the procedure. Proposes changes and reforms which may be made at the Inter-Governmental Conference of 1996.